Improving Junior High School Students' Writing Skills through the PQP Technique - Pasaribu, Baginda Iqbal; Abdullah, Umar; Amrina, Rizqy Dwi (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Writing skills are vital for English as a Foreign Language learners as the skills are beneficial for effective communication and analytical thinking. However, there is a lack of writing skills in KUD Pesari Kuni Muara Enim junior high school students. This research aimed to explore the effectiveness of the Praise, Questions, Polish (PQP) technique in improving students’ writing ability. The researchers employed a quasi-experimental design with a non-equivalent pretest-posttest arrangement involving 55 eighth-grade students from two classes of a private junior high school in KUD Pesari Kuni Muara Enim, with 27 students in the experimental group and 28 students in the control group. Data were gathered using tests administered both before and after the treatment. The hypothesis was tested by analyzing pre-test and post-test data using the independent sample t-test and paired sample t-test in the SPSS software. The research findings indicated a significant difference between the experimental group taught with the PQP technique and the control group receiving conventional instruction. Statistical analysis showed a significant difference in pre-test and post-test scores for both groups, with a significance level of p < 0.05. Paired-sample t-tests and independent-sample t-tests revealed that the difference between conventional and PQP methods was 0.003, while the difference in pre-test and post-test scores was 0.004. Thus, it can be concluded that the use of the PQP technique has a significant positive impact on students' writing skills.